Relaciones del Liderazgo Transformacional del Profesor con la Autoestima, la Autoeficacia Motriz, el Disfrute y la Intención de ser Activo en Estudiantes de Educación Física. - Sánchez-García, Carolina (UMA Editorial, 2025)
Physical activity during adolescence promotes health and well-being by reducing stress, improving neurocognitive and emotional well-being, and fostering social skills. Adolescents often fail to meet recommended activity levels, and Physical Education (PE) classes provide a unique opportunity to promote active lifestyles. The transformational leadership of PE teachers, characterized by idealized influence, motivational inspiration, intellectual stimulation, and individualized consideration, can positively impact students' self-esteem, motor self-efficacy, enjoyment, and intention to remain active. Research highlights that transformational leadership fosters positive experiences in PE, increasing intrinsic motivation, effort, and satisfaction. Teachers who inspire and support students create environments where enjoyment and self-confidence are prioritized, encouraging lifelong physical activity habits. Self-esteem, defined as self-worth based on experiences and emotions, improves through positive leadership, enhancing commitment to motor tasks and enjoyment. Similarly, motor self-efficacy, the confidence in one's physical abilities, predicts adherence to active behaviors. The studies included in this doctoral thesis reveal significant relationships between transformational leadership, self-esteem, motor self-efficacy, enjoyment, and the intention to remain active among adolescents. Motivational inspiration and intellectual stimulation were key predictors of these variables, with enjoyment emerging as the strongest mediator. Structural equation modeling confirmed that motor self-efficacy and enjoyment significantly mediate the relationship between transformational leadership and active intentions. The findings emphasize the importance of planning and promoting transformational leadership in PE to create supportive and enjoyable environments that enhance students' well-being and motivation.
Keywords: Educación física - Estudio y enseñanza - Tesis doctorales; Physical activity; Healthy lifestyle; Physical Education class; Transformational leadership; Adolescents